Pembuatan Mortar Geopolimer Berbasis Palm Oil Fly Ash-Grafena (Pofa-Grafena) Dengan Variasi Rasio Pofa/Pasir Dan Berat Grafena - Yola Bertilsya Hendri; Amun Amri; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Geopolymer mortar is a mortar produced by reacting a high concentrated alkaline solution with precursors containing high alumina and silica contents. The use of geopolymer mortar can replace the use of ordinary portland cement (OPC) in the construction industry. Thisresearch aims to synthesize palm oil fly ash (POFA) based geopolymer mortar with the addition of graphene nanosheets, to determine the effect of POFA-to-sand composition ratio, and variations of graphene to mechanical properties and morphology of geopolymer mortar. The research was conducted by varying the ratio of POFA-to-sand (1:0, 1:1, 1:2, and 2:1 by mass ratio), variations of graphene (0, 0,1, 0,35, and 0,5% by weight), curing time (24 h) and curing temperature (60℃). Scannning Electron Microscope (SEM) analysis showed that the addition of sand and graphene reduced the porosity of geopolymer mortar. The compressivestrength test results showed that the highest compressive strength (16,4 MPa) was obtained at POFA-to-sand ratio of 2:1 and 0,5% wt graphene content. While the lowest compressive strength (5,4 MPa) was obtained at the POFA-to-sand ratio of 1:2 and 0% wt graphenecontent.Keywords: alumina, silica, alkaline activator, crystalline, geopolymerization